PENGGUNAAN TEKNIK PERMAINAN “PETI MENULIS” UNTUK MENINGKATKAN KEMAMPUAN MENULIS MUFRODAT DI KELAS VII C MTs. NEGERI DONOMULYO - Barokatus solihah (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2016)
This research aims at improving the student's learning achievement in Arabic teaching and learning by implementing “Peti Menulis Game” to improve students’ writing of vocabulary The subjects of this research are the students of class VII C that consists of 24 students of Madrasah Tsanawiyah Negeri (MTsN) Donomulyo Nanggulan Kulon Progo in academic year of 2013/2014. The product of this research is to control “mufrodat”( vocabularies) for the students of class VII C The implementing of this game shows that there is the increased on students vocabularies. On the first cycle students’ activities are categorized enough on 55,05 %, the second cycle goes better on 70,72% and the third cycle is categorited good on 81,81%.